Effects of Storage Temperature and Duration on Flow Cytometry Analysis of Bone Marrow Aspirate Samples. (9th November 2022) - Chen, C; Cevallos, S; Zhou, Y
Abstract: Introduction/Objective: Multiparameter flow cytometry immunophenotyping is a powerful and indispensable tool in the diagnosis of hematologic malignancies, but its accuracy and precision are vulnerable to pre-analytical interferences. Acid-citrate-dextrose (ACD) is one of three main anticoagulants used for marrow collection. It offers better preservation and is commonly used for apheresis stem cell collection. However, ACD may alter the pH of short-draw samples. It is unclear how prolonged storage in ACD affects the results of flow cytometry testing. In this pre-analytical study, we characterized the effects of temperature and storage duration in bone marrow aspirate collected in ACD. Methods/Case Report: Five bone marrow specimens were collected in ACD and stored at 4°C or room temperature (RT), respectively. Aliquots of specimens were tested at 24, 48, and 72 hours. A flow cytometry panel including CD19, CD33, CD34, CD38, CD45, CD138, and 7-AAD was used to identify lymphocytes, monocytes, granulocytes, myeloid blasts, hematogones, and plasma cells. Absolute cell count, percentage of leukocytes, percentage of membrane- compromised cells (7-AAD bright), and mean-fluorescent-intensities were measured for each subset. The results of each storage condition were compared to the results on the day of sample collection. Results (if a Case Study enter NA): We found that granulocytes and plasma cells are most vulnerable to delayed testing, especially when stored at RT. Myeloid blasts, hematogones, monocytes, and lymphocytes were largely stable within 48 hours at 4°C or RT, but their relative representation in total leukocytes was affected by the diminished granulocytes. Variations in surface marker expression of CD45, CD38, and CD138 in the plasma cell subset were also noticed. This effect was less profound at 4°C than RT. Conclusion: We conclude that delayed testing of specimens collected in ACD within 72 hours does not significantly impact the results of flow cytometry testing for the commonly studied subsets, and 4°C may be a more robust and preferable method for storage.